Análisis de contenidos comunicacionales en medios digitales en el cantón Montalvo - Angamarca Padilla, Wilmer Stalin (2023)
The objective of this research was to analyze the quality of the contents broadcasted and the informative treatment that the digital media The Félix TV and Montalvo Noticias of the city that broadcast the information, understanding the great boom that the digital media have after the pandemic by the covid-19. Due to the Covid-19 pandemic, the consumption of digital platforms and the generation of content was strengthened, but many of these do not meet the parameters of journalistic quality established on the basis of an informative agenda and carried out by professionals in Communication or Journalism. Thus, through this case study conducted with a quantitative approach and with the research technique of surveys and its instrument the questionnaire to the population, it was identified the lack of credibility and quality of content that the digital media of the canton Montalvo present in relation to public opinion, establishing a result that the majority of 80% of respondents mentioned that they are not satisfied with the journalistic treatment that the digital media provide in relation to their communication agendas, also consider that the contents issued do not meet journalistic standards to meet the needs of objectivity, bias and truthfulness.